Potential of Essential Oil as Anti-Dandruff in Scalp Treatment Preparations - Detria Wulandari; Iyan Sopyan; Rifkarosita Putri Ginaris; Muhammad Faizal Fathurrohim; Ira Maya (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2022)
Most scalp problems in the community are dandruff. The most widely known microorganism that contributes to dandruff is Malassezia spp. The currently available treatment options for anti-dandruff are mostly synthetic substances. Unfortunately, these synthetic substances can cause various problems, such as side effects and drug resistance, especially the compliance of the patient. Herbal remedies that can be used to reduce the risks are essential oils. There are several essential oils that have been researched on anti-dandruff potential are Tea Tree, Lemongrass, Lavender, Rosemary, Eucalyptus, Coleus amboinicus, etc. The potential of essential oils as anti-dandruff ingredients in scalp remedies will be discussed in this article review. This article review was conducted using a comparative research method from a variety of sources, including online research journals and other sources. The outcome of this review article revealed that the previously mentioned essential oils have positive results in inhibiting the growth of the Malassezia sp., in its pure form, a combination of pure essential oils, or when in product form.